Sentikių Bažnyčia Lietuvoje 20-me amžiuje - Potašenko, Grigorijus (Lietuvos istorijos studijos, 1997)
This article is a short study of Church history of Old Believers, of relation between Old Believers Church and state in the independence Lithuania (1918-1940), Poland (district of Vilnius), and in Soviet Lithuania (1940-1941, 1944-1990). In the second half of the 17th century, Old Believers settlements were organized in Great Duke of Lithuania. After World War I, 35,000 Old Believers inhabited the Lithuanian republic. In 1922, Old Believers subordinated their communities to the Centrai Council of Old Beliefs Church in Lithuania in the matters of faith. Old Believers were recognized by the Lithuanian state as a separate persuasion. In the forties of the 20th century, there were 54 communities of Old Believers in Lithuania. In 1925, the First Congress of Polish Old Believers convened. The Congress agreed upon the official name of Old Believers – Pomortsy – Eastern Old Belief Church without ecclesiastic hierarchy. The organization of the Church and the internal statute was resolved. In 1928, Old Believers were recognized by the state as a separate persuasion. Generally, before World War II, over 50,000 Old Believers inhabited Poland. During World War II, some of the Old Believers joined the Red Army, others joined the underground army. Many Old Believers stayed in Lithuania. The Nazis deported some of them to forced labor camps. In the time of the war, some oratories were destroyed, and some Old Believers died. In 1987, there were 54 communities of Old Believers in Lithuania. Between 1944-1988, three Congresses of Old Belief Pomorskaya Church were held here. The High Council of Old Believers was the only religious-spiritual center of bespopovtsy pomortsy in the Soviet Union (till 1990).